Beyond Saccharomyces pastorianus for modern lager brews: Exploring non-cerevisiae Saccharomyces hybrids with heterotic maltotriose consumption and novel aroma profile - Gyurchev, Nikola Y.; Coral-Medina, Ángela; Weening, Susan M.; Almayouf, Salwa; Kuijpers, Niels G. A.; Nevoigt, Elke; Louis, Edward J. (Frontiers in Microbiology, 2022)
Non-domesticated, wild Saccharomyces yeasts have promising characteristics for beer diversification particularly when used in the generation of de novo interspecific hybrids. A major motivation for the current work was the question whether attractive novel Saccharomyces interspecific hybrids can be created for the production of exotic lager beers without using the genomic resources of the ale yeast Saccharomyces cerevisiae. Importantly, maltotriose utilization is an essential characteristic typically associated with domesticated ale/lager brewing strains. A high-throughput screening on nearly 200 strains representing all eight species of the Saccharomyces genus was conducted. Three Saccharomyces mikatae strains were able to aerobically grow on maltotriose as the sole carbon source, a trait previously unidentified for this species. Our screening also confirmed the recently reported maltotriose utilization of the S. jurei strain D5095T. Remarkably, de novo hybrids between a maltotriose-utilizing S. mikatae or S. jurei strain and the maltotriose-negative Saccharomyces eubayanus strain CBS 12357T displayed heterosis and outperformed both parents with regard to aerobically utilizing maltotriose as the sole source of carbon. Indeed, the maximum specific growth rates on this sugar were comparable to the well-known industrial strain, Saccharomyces pastorianus CBS 1513. In lager brewing settings (oxygen-limited), the new hybrids were able to ferment maltose, while maltotriose was not metabolized. Favorable fruity esters were produced, demonstrating that the novel hybrids have the potential to add to the diversity of lager brewing.